Single-cell RNA-seq uncovered hemocyte functional subtypes and their differentiational characteristics and connectivity with morphological subpopulations in Litopenaeus vannamei - Cui, Chuang; Tang, Xiaoqian; Xing, Jing; Sheng, Xiuzhen; Chi, Heng; Zhan, Wenbin (Frontiers in Immunology, 2022)
Hemocytes play central roles in shrimp immune system, whereas whose subclasses have not yet been completely defined. At present, the morphological classification of hemocytes is inadequate to classify the complete hemocyte repertoire and elucidate the functions and differentiation and maturation processes. Base on single-cell RNA sequencing (scRNA-seq) of hemocytes in healthy Litopenaeus vannamei, combined with RNA-FISH and flow cytometric sorting, we identified three hemocyte clusters including TGase+ cells, CTL+ cells and Crustin+ cells, and further determined their functional properties, potential differentiation trajectory and correspondence with morphological subpopulations. The TGase+ cells were mainly responsible for the coagulation, exhibiting distinguishable characteristics of hyalinocyte, and appeared to be developmentally arrested at an early stage of hemocyte differentiation. The CTL+ cells and Crustin+ cells arrested at terminal stages of differentiation mainly participated in recognizing foreign pathogens and initiating immune defense responses, owning distinctive features of granule-containing hemocytes. Furthermore, we have revealed the functional sub-clusters of three hemocyte clusters and their potential differentiation pathways according to the expression of genes involved in cell cycle, cell differentiation and immune response, and the successive differentiation and maturation of hyalinocytes to granule-containing hemocytes have also mapped. The results revealed the diversity of shrimp hemocytes and provide new theoretical rationale for hemocyte classification, which also facilitate systematic research on crustacean immunity.